Uniform Statistical Convergence on Time Scales. (17th June 2014) - Altin, Yavuz; Koyunbakan, Hikmet; Yilmaz, Emrah
Abstract : We will introduce the concept of m - and ( λ, m ) -uniform density of a set and m - and ( λ, m ) -uniform statistical convergence on an arbitrary time scale. However, we will define m -uniform Cauchy function on a time scale. Furthermore, some relations about these new notions are also obtained.